Intercultural Counseling: A Perspective to Favor Coexistence in Multicultural Contexts - Garita Pulido, Ana Victoria (2013)
This article refers to the professional practice of Counseling with an intercultural perspective to face multicultural contexts. The paper reflects on coexistence as a social challenge in multicultural contexts and analyzes the importance of culture in the creation of personal identity, and the resulting need for it to be considered in every counseling action. Principles, purposes and characteristics of the intercultural perspective are presented as an integrative model for the attention of cultural diversity, as well as some arguments to define intercultural counseling.  The attitude, knowledge and skills to be developed by counselors to be interculturally competent are also mentioned in the paper. In addition, the study lists all those skills that should be promoted in the counselor’s clients to create a positive coexisting interaction based on their differences.